PENGARUH SIKAP, NORMA SUBYEKTIF DAN KONTROL PERILAKU YANG DIRASAKAN TERHADAP MINAT BERWIRAUSAHA DENGAN PENDEKATAN THEORY OF PLANNED BEHAVIOUR (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Unika Santo Thomas Medan) - Simanihuruk, Peran; Tamba, Darwis; Sagala, Roslinda (Jurnal Manajemen dan Bisnis, 2021)
The research objective was to analyze the influence of attitudes, subjective norms and perceived behavioral control on student interest in entrepreneurship. The number of samples was 96 students using questionnaire data collection methods and documentation and analysis techniques for the application of the Theory Of Planned Behavior model. The results showed that B Â»BI = 0.443Ab + 0.299SN + 0.257 PBC with w1 = 0.443 or 44.3%, w2 = 0.299 or 29.9% and W3 = 0.257 or 25.7%. This means that attitudes, subjective norms and perceived behavioral control have a positive effect on interest in entrepreneurship. However, what is more influential on the interest in entrepreneurship is the attitude then subjective norms. To further increase student interest in entrepreneurship, it is better if you need to increase the number of SKS in Entrepreneurship courses and make various training to create products, how to determine the cost of products, how to sell / market products, how to promote products and distribute them to increase student insight so that entrepreneurial interest will be formed his mind. With this, students who have graduated are not merely job seekers but as job creators.